Assessing the function of pneumococcal neuraminidases NanA, NanB and NanC in in vitro and in vivo lung infection models using monoclonal antibodies. Issue 1 (31st December 2018) - Janesch, Philipp; Rouha, Harald; Badarau, Adriana; Stulik, Lukas; Mirkina, Irina; Caccamo, Marisa; Havlicek, Katharina; Maierhofer, Barbara; Weber, Susanne; Groß, Karin; Steinhäuser, Jacqueline; Zerbs, Manuel; et al.
ABSTRACT: Streptococcus pneumoniae isolates express up to three neuraminidases (sialidases), NanA, NanB and NanC, all of which cleave the terminal sialic acid of glycan-structures that decorate host cell surfaces. Most research has focused on the role of NanA with limited investigations evaluating the roles of all three neuraminidases in host-pathogen interactions. We generated two highly potent monoclonal antibodies (mAbs), one that blocks the enzymatic activity of NanA and one cross-neutralizing NanB and NanC. Total neuraminidase activity of clinical S. pneumoniae isolates could be inhibited by this mAb combination in enzymatic assays. To detect desialylation of cell surfaces by pneumococcal neuraminidases, primary human tracheal/bronchial mucocilial epithelial tissues were infected with S. pneumoniae and stained with peanut lectin. Simultaneous targeting of the neuraminidases was required to prevent desialylation, suggesting that inhibition of NanA alone is not sufficient to preserve terminal lung glycans. Importantly, we also found that all three neuraminidases increased the interaction of S. pneumoniae with human airway epithelial cells. Lectin-staining of lung tissues of mice pre-treated with mAbs before intranasal challenge with S. pneumoniae confirmed that both anti-NanA and anti-NanBC mAbs were required to effectively block desialylation of the respiratory epithelium in vivo . Despite this, no effect on survival, reduction in pulmonary bacterial load, or significant changes in cytokine responses were observed. This suggests that neuraminidases have no pivotal role in this murine pneumonia model that is induced by high bacterial challenge inocula and does not progress from colonization as it happens in the human host.